Handbook of research on assertiveness, clarity, and positivity in health literacy - Almeida, Cristina Vaz de 1964-; Ramos, Susana 1967- (IGI Global, 2022)
"This book provides relevant theoretical frameworks and the latest results of empirical research in the domain of health literacy and the competencies of assertiveness, clarity of language and positivity in development and results for society, even beyond health"--